A Baby thesis in the application of operations research to Swift Foods, Inc. Feedmill, Cagayan de Oro City - Sagun, Pinky B. (Diliman, Quezon City College of Engineering, 2002)
Swift Foods Inc. Feedmill of Cagayan de Oro was established in 1989 after a thorough study had been made when the SFI Feedmill of Cebu could no longer accommodate the increasing demands of feeds both in Visayas and in Mindanao Regions. At present, Swift Foods Inc. Feedmill Cagayan de Oro is distributing feeds in Bukidnon, Butuan, Cagayan de Oro, Dipolog, and Pagadian. While SFI Feedmill Cebu is distributing feeds in Davao, General Santos, and other parts in the Visayas Regions. Since the management still follows the traditional distribution set-up in their establishment, the manager's main concern right now is to find another feasible way of distributing their products to each destination. The main objective of the study is to determine an appropriate distribution plan that will give maximum profit to the firm. Three alternatives have been formulated: (1) fully utilizing the CDO plant, aside from the Cebu plant; (2) consider an expansion of the CDO plant; and (3) consider another plant in Davao, aside from the plant in CDO. Thus, building another plant in Davao to supply its very own place and its neighboring city, General Santos, gives the management the best distribution plan of feeds. The company can save more if they will consider building another plant in Davao, and allow the CDO plant to render services exclusively for Bukidnon, Butuan, Dipolog, and Pagadian. It is the main purpose of this study to give management a clear picture with regards to choosing an appropriate distribution plan for their product. Thus, it is necessary to weigh various alternatives before any decision is made. Operations Research has proven itself to be a valuable technique for analyzing manufacturing systems because it allows the manager to obtain a system-wide view of the effect of changes on his manufacturing system.
Submitted in partial fulfillment of the course requirements in MS Industrial Engineering
Keywords: Swift Foods Incorporated Feedmill; Mills industry